2014
DOI: 10.1080/07294360.2014.934663
|View full text |Cite
|
Sign up to set email alerts
|

Why start a higher degree by research? An exploratory factor analysis of motivations to undertake doctoral studies

Abstract: The AM is defined by the National Information Standards Organization as: "The version of a journal article that has been accepted for publication in a journal."This means the version that has been through peer review and been accepted by a journal editor. When you receive the acceptance email from the Editorial Office we recommend that you retain this article for future posting.Embargoes apply if you are posting the AM to an institutional or subject repository, or to academic social networks such as Mendeley, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 37 publications
8
85
0
11
Order By: Relevance
“…Moreover environmental influences should also be taken into account. For instance, research has shown that encouragement from professors might stimulate students to enter graduate school (Eagan Jr et al, 2011;Dasan, 2013;Guerin et al, 2015), the traditional way to a career as a researcher, and that the socialization by family and peers might have an important impact on students' progress (Lamport, 1993;Zafira, 2012;Guerin et al, 2015). Labini and Zinovyeva (2011) also stated that the quality of the research of the university was an important stimulus for students to enroll in a PhD program, and this was more so in sciences, medicine, and engineering.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover environmental influences should also be taken into account. For instance, research has shown that encouragement from professors might stimulate students to enter graduate school (Eagan Jr et al, 2011;Dasan, 2013;Guerin et al, 2015), the traditional way to a career as a researcher, and that the socialization by family and peers might have an important impact on students' progress (Lamport, 1993;Zafira, 2012;Guerin et al, 2015). Labini and Zinovyeva (2011) also stated that the quality of the research of the university was an important stimulus for students to enroll in a PhD program, and this was more so in sciences, medicine, and engineering.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Woolnough (1994, as quoted in Kamphuis, 2007), Zafira (2012), and Guerin et al (2015) state that the attitudes of students towards science and technology as a vocation and as a domain of study also depend on the home culture. Students who grow up in families where science and research receive some recognition, show a more positive attitude towards science (although this is less so for female students) or are more interested in attending graduate school.…”
Section: Journal Of Education and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, doctoral students are interested in learning skills that are not necessarily those for which there is a demand in non-academic sectors, and this has been discussed in the literature as a major challenge to the employment of doctorate holders in non-academic sectors (see De Grande et al, 2014). It is also clear that financial motivation has not been critical for many doctoral applicants (Guerin et al, 2015;Roach and Sauermann, 2010;Zhou, 2014), although studies present mixed findings concerning the salary premium of holding a PhD when compared to other higher education degrees (e.g., Casey, 2009 vis-a-vis Mertens andRobken, 2013).…”
Section: The Changing Nature Of Phdsmentioning
confidence: 99%
“…These motivations are less related with financial incentives, downstream work and access to resources (Guerin et al, 2015;Roach and Sauermann, 2010;Zhou, 2014). In general, doctoral students are interested in learning skills that are not necessarily those for which there is a demand in non-academic sectors, and this has been discussed in the literature as a major challenge to the employment of doctorate holders in non-academic sectors (see De Grande et al, 2014).…”
Section: The Changing Nature Of Phdsmentioning
confidence: 99%